Compressive and transverse shear behaviour of novel FRP-UHPC hybrid bars. (1st February 2022) - Zeng, Jun-Jie; Ye, Yu-Yi; Quach, Wai-Meng; Lin, Guan; Zhuge, Yan; Zhou, Jie-Kai
Abstract: Fibre-reinforced polymer (FRP) bars have become increasingly popular as internal reinforcement in reinforced concrete (RC) structures due to their excellent corrosion resistance. However, the compressive strength of FRP bars is generally much inferior to their tensile strength due to fibre micro-buckling under compression, and their transverse shear performance is much inferior to that of steel bars with the same diameter. To this end, a novel form of steel-free hybrid bars, which consist of an outer FRP confining tube, a central FRP bar and a layer of ultra-high performance concrete (UHPC) (without steel fibres) in the annular space between them (referred to as FRP-UHPC hybrid bars), have been proposed. In this study, compressive and transverse shear behaviour of FRP-UHPC hybrid bars have been investigated via experimentation. The key test variables include fibre winding angles of the FRP tube, fibre types of the FRP tube, the FRP tube thickness and the diameter of the central FRP bar. The test results confirm the validation of the novel hybrid bars: i) the compressive stress-strain curves of hybrid bars exhibit a ductile behaviour with a strain hardening segment, and the compressive behaviour of the central FRP bar in hybrid bars is superior to that of FRP bars in isolation; ii) the stress-strain response of hybrid bars can be designed to meet an elastic-plastic response with a post-yielding strain-hardening response; and iii) the transverse shear performance of hybrid bars is much better than that of FRP bars in isolation due to the contribution of FRP-confined UHPC section.